From Politics to Economic Cooperation: Islam as Identity of Foreign Policy in Jokowi Era - Karisma, Gita; Rachmawati, Tety (Journal of Islamic World and Politics, 2025)
The issue of Islam in Indonesia's foreign policy is generally used as a tool to achieve political interests. At the beginning of independence, Arab countries were the main supporters of Indonesian independence. The rest of the time, the issue of Islam was also used by leaders as a tool to gain political support at the domestic level, as well as to reduce the pressure of public opinion. This article aims to look at the discourse and orientation of Indonesia's foreign policy regarding Islamic issues in the Jokowi era. Using a discourse analysis method, the article found that as a democratic country, the discourse that Indonesia has always built regarding Islam is a humanitarian issue. In addition, there is a transformation occurring that Islam has begun to be used to encourage economic cooperation and build the image of Indonesia's leadership among Muslim countries. Indonesia also began to move from using Islamic discourse only as a political tool, and now, it is used as an opportunity to build cooperation with the Muslim world.